STARTING A DIGITAL MARKETING FROM TIKTOK : BEING A MILLENIAL INNOVATING SOCIOPRENEUR - Jihan Sabila; Ritha Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to show how to become a millennial sociopreneur who innovates through digital marketing on social media TiktTok. This is characterized by the rapid integration of digital technology in various aspects of life, such as industry, government, education, entrepreneurship and others. The role of sociopreneurs is becoming increasingly important because digital technology allows them to create a greater and more efficient social impact. Thus, TikTok can be a powerful tool for sociopreneurs in achieving their social goals, building awareness, and mobilizing support from society at large in this digital era. The Industrial Revolution 4.0 era also provides platforms such as TikTok with strong changes for sociopreneurs to create significant social impacts in more efficient and innovative ways. By using a qualitative research method, namely observation based on direct experience of the object to be researched, in this case the author observes the activities carried out by Indonesian sociopreneurs who have run their businesses and made changes. And the results are like the heroic action of the Pandawara Group which uses Tiktok as its marketing medium to encourage all people to care about the surrounding environment.